Policy and Governance for Electricity Supply in Australia: Public or Private Interest? - Aulich, Chris; Wettenhall, Roger (The journal of contemporary issues in business and government, 2017)
The National Energy Market (NEM) introduced in 1998 sought to connect the electrically linked states and territories of eastern and southern Australia in a system which embraced the generation, transmission, distribution and marketing of electric power. The ‘market’ unbundled the vertically integrated public enterprises then operating at state and territory levels and substituted a complex system comprising several hundred entities functioning through all phases of the industry and demanding significant coordination and regulation to ensure effective operation. This article looks first at the structural arrangements, and examines private, public and public-private elements of the mix. It then considers a set of public interest tests for the industry first proposed as early as 1956, and asks whether the NEM arrangements satisfy those tests. It concludes that they do not.